Fluorine recovery from etching wastewater through CaF2-based near-infrared photocatalyst synthesis. (20th February 2018) - Yin, Changkai; Yu, Sen; An, Bairui; Lou, Ziyang; Huang, Shouqiang; Yuan, Haiping; Zhu, Nanwen
Abstract: Fluorine in etching wastewater is an important F resource, and the development of a high value-added fluorine based compounds could benefit for the fluoride resource saving and the reduction of fluoride effluent. In this work, F from etching wastewater was recovered by composites of CaF2 and CaSO4, which was used to prepare as the near infrared photocatalyst of Tm 3+ /Yb 3+ co-doped ((CaF2 /CaWO4 )@Bi2 WO6 ) (TY-CCB). It was found that CaWO4 was fabricated by the slow release of Ca 2+ ions from CaSO4 particles according to XRD and XPS results, and the heterostructure between CaWO4 and Bi2 WO6 were formed in the TY-CCB composite with flat-shape morphology, which could improve the photocatalytic activity. The upconverted UV (364 nm) and blue (484 nm) light were observed upon 980 nm NIR irradiation, combined with the extended absorption band of 519 nm in TY-CCB. For the degradation of methyl orange (MO) and salicylic acid (SA), the corresponding degradation rate of 0.44 and 0.42 mg L −1 ·h −1 were obtained after 3 h under NIR light irradiations, and both of them increased to 2.78 and 1.74 mg L −1 ·h −1 under UV–vis–NIR light irradiations, respectively. Fluorine recovery through the preparation of TY-CCB upconversion photocatalyst was a mutually beneficial approach. Graphical abstract: Image 1 Highlights: Fluorescent reagent of Tm 3+ /Yb 3+ -CaF2 /CaSO4 was fabricated from etching wastewater. CaSO4 was substituted by CaWO4 in synthesis process of TY-CCW . High value-added F based near-infrared photocatalyst of TY-CCB was synthesized. The separation process of CaF2 was avoided through the co-generation of Bi2 WO6 .